KAJIAN SISTEM KERJA ALAT MUAT DAN ALAT ANGKUT PADA PENGUPASAN OVERBURDEN DENGAN PENERAPAN METODE ANTRIAN DI PIT TAMAN TAMBANG AIR LAYA PT.BUKIT ASAM (PERSERO) TBK - Dwi Rahmi Elvionita; Dedi Yulhendra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Pit Taman is a mining location that located inPT.BAarea, on the process of stripping overburden in the Pit Taman uses 6 units of conveyance and 1 unit loading equipment. The production target of overburden stripping in November is not reached. This is due to the lack of composition of mechanical units and the number of waiting times that occur in the conveyance. The purpose of this research is to calculate the productivity of each fleet in the Pit Taman, to calculate the compatibility of tools in Pit Taman, to gain effort and to reduce queue time at overburden production in the Pit Taman and to get match factor equal to 1.In this study combined between the theory with field data, so that in the approach to problem solving. And the results of data processing will be analyzed for subsequent to be generated a recommendation.Based on the research results can be concluded. First, the productivity komatsu PC 1250 on fleet 1 is 473,87 bcm / hour and productivity komatsu HD 785 is 109,34 bcm / hour. In fleet 2 productivity komatsu PC 2000-1 is 703.50 bcm / hour and komatsu HD 785 is 174.23 bcm / hour. In fleet 3 productivity komatsu PC 2000-2 is 730.64 bcm / hour and komatsu HD 785 is 186.15 bcm / hour. Second, the composition of the available equipment of Fleet 1 is 1 loader and 6 conveyance equipment, Fleet 2, 1 loader and 6 conveyance, Fleet 3.1 loader and 6 conveyance. Third, the effort to reduce the queue time improves the composition of the tool to MF = 1. Fourth, the calculation analysis MF = 1 on fleet 1 = 5 units of HD, fleet 2 = 4 units, fleet 3 = 4 units.Key words :production,macth factor,queue teori